2015
DOI: 10.1177/2055102915615338
|View full text |Cite
|
Sign up to set email alerts
|

Using computerized text analysis to assess communication within an Italian type 1 diabetes Facebook group

Abstract: The purpose of this study was to assess messages posted by mothers of children with type 1 diabetes in the Italian Facebook group “Mamme e diabete” using computerized text analysis. The data suggest that these mothers use online discussion boards as a place to seek and provide information to better manage the disease’s daily demands—especially those tasks linked to insulin correction and administration, control of food intake, and bureaucratic duties, as well as to seek and give encouragement and to share expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…As suggested by findings regarding utility of social media, web‐based resources appeared to be a useful strategy for engaging individuals with T1DM and for providing emotional support and information exchange . Social media use (Facebook and Skype) and online health communities allowed adolescents with T1DM and their parents to gain and share diabetes knowledge and information, to cope better with their daily life, to improve self‐management, and to achieve diabetes control . In addition, as shown by previous research, chat line participation was found to be a useful tool for adolescents to improve coping with T1DM and gaining metabolic control (Hb1Ac values) and quality of life as well …”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…As suggested by findings regarding utility of social media, web‐based resources appeared to be a useful strategy for engaging individuals with T1DM and for providing emotional support and information exchange . Social media use (Facebook and Skype) and online health communities allowed adolescents with T1DM and their parents to gain and share diabetes knowledge and information, to cope better with their daily life, to improve self‐management, and to achieve diabetes control . In addition, as shown by previous research, chat line participation was found to be a useful tool for adolescents to improve coping with T1DM and gaining metabolic control (Hb1Ac values) and quality of life as well …”
Section: Introductionmentioning
confidence: 66%
“…28 Social support and information were the two prominent aspects of messages posted by the adolescents in public web-based forums 12 as well as in an active Facebook diabetes groups where lifestyle information, peers personal experiences, emotions, opinions, and advice were frequently exchanged by members. 16,29 Similarly, in three…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same authors also analyzed concussion-related Web sites and found that the quality of online information available for consumers was inconsistent, 30 although further investigations 31,32 have been conducted into the content of concussion-related information on Twitter and YouTube. Facebook support groups have been shown to be beneficial for a range of conditions, including breast cancer 33 and diabetes, 34 and for the parents of preterm infants. 35 The use of innovative strategies and technologies to assist in the diagnosis and management of concussion has been recognized and recommended in the Concussion in Sport (CIS) consensus statement 3 and the National Athletic Trainers' Association position statement.…”
mentioning
confidence: 99%